(untitled) (Modern education and development, 2025)
В данной статье мы подробно рассмотрим основные послеоперационные осложнения, которые могут возникнуть в результате хирургического вмешательства при рубцовом стенозе трахеи. Также будут предложены рекомендации по профилактике этих осложнений, что позволит повысить безопасность и эффективность хирургического лечения. Правильный подход к предоперационной подготовке, выбору методов анестезии и мониторингу состояния пациента в послеоперационный период может существенно снизить риск возникновения осложнений и улучшить результаты лечения. In this article, we will thoroughly examine the main postoperative complications that may arise as a result of surgical intervention for scar stenosis of the trachea. Recommendations for the prevention of these complications will also be provided, which will enhance the safety and effectiveness of surgical treatment. A proper approach to preoperative preparation, the selection of anesthesia methods, and monitoring the patient’s condition in the postoperative period can significantly reduce the risk of complications and improve treatment outcomes.